Poetische Gerechtigkeit - Donat, Sebastian; Richter, Virginia; Packard, Stephan; Lüdeke, Roger (De Gruyter, 2023)
The discussions on an ethics of literature and a specifically aesthetic form of justice make it clear: the question of the aesthetic and ethical valuation and evaluation of literature has recently moved back into the centre of interest in the humanities and cultural studies. This volume brings together contributions on the themes of crime/punishment, penance/mercy or virtue/reward.